Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations DEVONIAN ASSOCIATION FOR CRIPPLES' AID. MEDICAL REPORT. In order that the special problems of the orthopaedic work of the Association during the past year may be understood, it is necessary to realize that this work resolves itself into two main types. Firstly, there is the necessity for the treatment of diseased conditions of the bones, joints and muscular system, and, secondly, the treatment of mechanical defects, the sequel of such diseased conditions. These two aspects are often closely interwoven, and the word treatment throughout implies a considerable amount of preventive work. These points are well illustrated in diseases such as tuberculosis of joints and infantile paralysis. In the active or acute stages these conditions may require many months in Hospital, while for the treatment of mechanical defects a few weeks will often suffice. During 1932 an effort has been made to deal with the amount of work in the second category, the result of old-standing disease, by transferring such cases at an early date from the Hospital to their homes and providing skilled after-care at the Clinics. This has enabled the special facilities of the Hospital to be used for a larger number of cases, more intensive work has been done and the cost has been less per patient. The average duration of Hospital treatment, though less than in previous years, is still relatively long and is, of course, due to the great time necessary in the care of patients belonging to the first type mentioned above. The number of cases belonging to the second type should in the course of a few years show a relative diminution as the result of the provision of orthopaedic facilities in Devonshire in recent years. A large proportion of the cases now under care are those whose diseases originated from five to fifteen years ago when these facilities were lacking. Once more it is necessary to stress that about 85 per cent of crippling conditions are due to disease not to inherited defects, and that these diseased conditions are favoured by over-population and defective hygiene. The responsibilities assumed by the State for the rehabilitation of such children by giving them something like an equal chance with their fellows, is a necessary link in the chain that is lifting us from the realms of a C3 nation, and its cost is infinitesimal when considered in terms of battleships or even with the cost of mentally defectives. Enough has been said to indicate that the Princess Elizabeth Orthopaedic Hospital has been a very busy place during the past year, and a special word of appreciation is due to Matron and her Staff for the manner in which difficulties have been met. One cannot speak too highly of their efficient devotion to the job in 13 292/841.51/2/2